Unions among people of the same sex (Revista da Faculdade de Direito, Universidade de São Paulo, 1999)
Our society watches, at present, the partnership phenomenon, between people of the same sex, living together or not, for a long period of time. This "union" has no similarity to the "civil marriage", ruled by the Civil Code, which systematic indicates the heterosexuality as an essential conjecture. It is true that the homosexual marriage is admitted in some European countries, like Denmark, Norway and Sweden. In Netherlands, some mechanisms were developed to make the registration of those unions possible, what had already occurred in San Francisco, United States of America. In the same way, if we think about a simple partnership of two persons of the same sex, it can not configure what we call "stable union", "concubinage", that is represented when a man and a woman live together, as husband and wife, concerned with family constitution, without being legally married. Among us, there is a law Project, n. 1.151/95, created by a state deputy, Mrs. Marta Suplicy, that aims the regulation of the partnership between people of the same sex, that is analyzed, in this piece of work. This partnership, according to the mentioned project, will be established with its registration (tittle-deed), at the "Civil Register Office". This project creates a discriminated "civil status", what, curiously, does not happen to the concubinage. The partners are able to sum their economies to the acquisition of their properties, specially of their home, that is guaranteed as a homestead. The health plan and the blanket insurance, contracted by one of the partners will benefit the other. There are some restrictions, for example, adoption, which will not be authorized to both of registered partners.